Transversal competences and employability: comparing in-person learning and distance education - Abhinandan Kulal; Sahana Dinesh; Abhishek N; Habeeb Ur Rahiman (Cogent Education, 2023)
AbstractThe demand for distance education has been increasing over the years, and this has gained momentum especially in the post-pandemic period. This development has caused a debate among the academicians as to whether distance education mode serves the real purpose of education as In-person learning does. Even though the method of schooling is not a consideration in most firms’ hiring decisions, the level of employability skills and competency are critical to landing a job in any sector. The primary goal of this study was to determine whether the mode of education caused a substantial difference in the competency and employability skills of the graduates/students. For this purpose, a sample of 350 In-person learning course students and 112 distance education students from Karnataka, India, was used in the study. Employability skills were measured using standard instrument with 10 dimensions and competency levels were measured using standard SLC Self-Evaluation Measurement with eight dimensions. This study found that the education method significantly impacts students’ competency and employability skills. Further, it demonstrates that distance education students have a higher competency level than In-person learning students. Conversely, students with In-person learning showed a higher level of employability skills. Distance education, however, is lacking in developing employability skills for various reasons. Nevertheless, using the right ed-Tech tools and software in distance education could boost effectiveness and keep the learners engaged and motivated.